Schmitt & Arendt: um diálogo sobre a constituição do político - Felipe Daniel Amorim Machado (2012)
This dissertation presents a possible dialogue between the German writers Carl Schmitt and Hannah Arendt on politics. Both, from the critique of liberalism, sought for the recognition of a locus for the political, arriving, however, on completely opposite ideas. Schmitt sees the politics in the homogeneity capable of generating unit, which, in turn, enables a certain political unity to make the distinction friend / enemy, being this the real character of the political. Arendt based his understanding on the concept of free action, i.e., an action that is an end in itself, that does not bind the reasons, but is set up on a principle that permeates it, being this the principle of freedom. Thus, every action seeks freedom, being precisely this the purpose of the politics, since, for the author, politics is the action in concert that aims to define the best paths to a political community. While Schmitt defines the politician through homogeneity, Arendt sees its plurality, i.e., in the multiplicity of the different people that are equalized in the public scene, which, in Arendts understanding, is the domain of politics. In building these conclusions the text presents, in his first chapter, an overview of Schmitts ideas, proceeding, in the sequence, to the musings of Arendt. Finally, the arguments of both authors on the definition of being a politician today are confronted. Despite the importance of understanding Schmitt and Arendt, in modern times they have no application in their pure states. In times in which the dichotomy friend/enemy returns to the political scene, as for example in the conflicts and separatist movements in the discourse of criminal law maximum or the enemy, among others, new perspectives on the concepts on the political are necessary but they are however, impossible to be made without returning to the insights of Carl Schmitt and Hannah Arendt.